2014
DOI: 10.1007/s10067-014-2676-1
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic polyangiitis associated with pulmonary fibrosis

Abstract: Microscopic polyangiitis (MPA) is a systemic necrotizing vasculitis characterised by inflammation of the small blood vessels, the absence of granulommas on histopathological specimens, with few or no immune deposits and the presence of circulating anti-neutrophil cytoplasmic antibodies (ANCAs). The classic pulmonary manifestation is diffuse alveolar haemorrhage (DAH), but its association with pulmonary fibrosis (PF) has been increasingly reported and may be the first manifestation of MPA. Our aim was to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
62
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(78 citation statements)
references
References 20 publications
10
62
0
6
Order By: Relevance
“…PF has been reported in 23% of GPA cases [52] and in 2.7–45% of MPA patients. In these cases, interstitial disease was usually identified at disease onset [7,11,1720,48,53,54]. Importantly, there is a significant predominance of MPO-ANCA in published series, i.e., 46–71% of all cases compared to 0–29% for PR3-ANCA [13,27,51,52,5456].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…PF has been reported in 23% of GPA cases [52] and in 2.7–45% of MPA patients. In these cases, interstitial disease was usually identified at disease onset [7,11,1720,48,53,54]. Importantly, there is a significant predominance of MPO-ANCA in published series, i.e., 46–71% of all cases compared to 0–29% for PR3-ANCA [13,27,51,52,5456].…”
Section: Epidemiologymentioning
confidence: 99%
“…Of relevance, frequency of ILD in ANCA vasculitis seems to be higher in Japan than in Western populations [17,18,20,54,55,60]. Reasons for this particular association may include a higher prevalence of MPO-ANCA positivity and increased frequency of lung involvement and diffuse alveolar hemorrhage [11,61,62].…”
Section: Epidemiologymentioning
confidence: 99%
“…Pulmonary fibrosis may precede other disease manifestations by a range of 5-108 months, but would not occur after the diagnosis of MPA [65,67]. The prognosis of MPA with pulmonary fibrosis is worse than that of MPA without pulmonary fibrosis and seems to be better than that of patients with idiopathic pulmonary fibrosis [65,67,68].…”
Section: Presentation and Diagnosismentioning
confidence: 99%
“…In a long-term retrospective study over a 15-year period in 28 patients with MPA, pulmonary fibrosis was identified in 9 patients (32%) and DAH was present in 11 cases (39%). A definite or possible usual interstitial pneumonia pattern was present in 8 cases (88%) and was associated with poor prognosis [65]. In another study of interstitial pneumonia with anti-myeloperoxidase-ANCA, 8 patients had a usual interstitial pneumonia pattern accompanied by areas of nonspecific interstitial pneumonia pattern and 1 patient had diffuse alveolar damage [66].…”
Section: Presentation and Diagnosismentioning
confidence: 99%
See 1 more Smart Citation